Analysis of a new standing passenger seat design for commercial transport aircraft - Mohamad Nor, Ahmad Redzman; Romli, Fairuz Izzuddin (Asian Research Publishing Network, 2023)
In order to have profitable flight operations, many airlines have used high-density passenger cabin design and arrangement. By doing this, more passengers can be accommodated inside the cabin per flight, hence reducing the overall flight costs per passenger. With conventional aircraft seats, the seat pitch is progressively reduced over the years to accommodate additional passengers into the cabin and this has created high flight comfort issues among the passengers. Reduced seat pitch also means that available legroom at each seat becomes smaller, which leads to discomfort due to inadequate space for many passengers in their sitting positions. For short-haul flights, the standing passenger cabin concept has been explored and proposed to help resolve this issue. Since passengers will require less legroom space in their standing positions, it is possible to have reduced seat pitch (hence more passengers) and acceptable comfort. A proposed standing passenger seat design is studied in this work to establish and support its suitability to be used in the standing passenger cabin concept. Finite element analysis is conducted to demonstrate its ability to fulfill the strength requirements imposed by the aviation authority. Furthermore, several design improvements have also been made to minimize its weight while still satisfying the strength requirements. The final standing passenger seat design has been shown to have adequate structural strength to cope with the requisite 9-g loading and a mass of about 11.7 kg which is lower than most conventional aircraft seats. All in all, this indicates that the proposed standing seat design has a good potential to be applied for air transportation and further supports the future implementation of the standing cabin concept. The final design from this study can be further refined in future studies to improve its characteristics.